Unjuk Kerja Desain Prototype Penepat Las dan Bor Bermagnet Berdasarkan Analisis Ergonomi dengan Metode Quick Exposure Checklist - Piyata Wira Yonatan Sitohang; Irawan Malik; Sairul Effendi (Politeknik Negeri Sriwijaya, Indonesia, 2024)
This study aims to develop a prototype design for an ergonomic welding and drilling clamping tool and evaluate its performance by analyzing relevant ergonomic aspects using the Quick Exposure Checklist method. The data utilized encompasses primary data obtained through observations, literature reviews, questionnaires, and field studies. The findings of this research indicate that the resulting prototype design for the welding and drilling clamping tool exhibits a good level of ergonomics, with the ergonomic evaluation test results reaching 37%. This value is slightly below the recommended action limit of 40%, indicating that the tool meets the safe ergonomic criteria based on the Quick Exposure Checklist method.